2020
DOI: 10.21203/rs.3.rs-53325/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differences in [18F]-FDG uptake in BAT of UCP1 -/- and UCP1+/+ during adrenergic stimulation of non-shivering thermogenesis

Abstract: Background Brown adipose tissue (BAT) is a fat tissue found in most mammals that helps regulate energy balance and core body temperature through a sympathetic process known as non-shivering thermogenesis. BAT activity is commonly detected and quantified in [18F]FDG positron emission tomography/computed tomography (PET/CT) scans, and radiotracer uptake in BAT during adrenergic stimulation is often used as a surrogate measure for identifying thermogenic activity in the tissue. BAT thermogenesis is believed to be… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…As a result, a wide range of conclusions about BAT distribution is inevitable when quantifying this tissue with 18 F-FDG standardized uptake values [11,12]. Additionally, although 18 F-FDG-PET has suggested that BAT activity is significantly lower in patients with obesity compared with lean patients [13], the dissociation between BAT activity and glucose uptake has demonstrated that these results may not be reliable [9,10,14]. Computed tomography (CT) and magnetic resonance imaging have also been explored as a method of locating and quantifying BAT [15,16], but their results depend on BAT hydration [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, a wide range of conclusions about BAT distribution is inevitable when quantifying this tissue with 18 F-FDG standardized uptake values [11,12]. Additionally, although 18 F-FDG-PET has suggested that BAT activity is significantly lower in patients with obesity compared with lean patients [13], the dissociation between BAT activity and glucose uptake has demonstrated that these results may not be reliable [9,10,14]. Computed tomography (CT) and magnetic resonance imaging have also been explored as a method of locating and quantifying BAT [15,16], but their results depend on BAT hydration [17].…”
Section: Introductionmentioning
confidence: 99%
“…The use of NHPs in this study is motivated by their phylogenetic similarity with humans in terms of adipose distributions and progression of obesity and metabolic diseases [29]. In contrast to mice, which tend to have BAT predominantly concentrated in the interscapular region [14,19,26], humans and NHPs have very similar anatomical distributions of BAT, with the main depots located in the supraclavicular and axillary regions [30,31]. Rhesus and vervet monkeys, in particular, spontaneously develop obesity and diabetes as they age at prevalence rates comparable to that of humans [31].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown by indirect calorimetry that [ 18 F]FDG uptake in brown adipose tissue is proportional to the amount of non-shivering thermogenesis; however, insulin-resistant individuals accumulate less [ 18 F] FDG than their insulin-sensitive counterparts [19,20]. Furthermore, [ 18 F]FDG uptake in response to β3AR agonists is unaffected in UCP1 knockout mice despite defective BAT thermogenesis [21]. ese findings suggest that [ 18 F]FDG uptake may not be always associated with UCP1-mediated thermogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Six mice were assessed by 18 F-FDG PET/CT at Week 0 (before tamoxifen induction) and Week 1 (after tamoxifen induction) following an established procedure 26 . In brief, each mouse was orally administered with a contrast agent (Iohexol, 150 mg/ml, 0.05 ml) under light anesthesia with isoflurane for visualization of the esophagus under contrast-enhanced CT. About 350 µCi of 18 F-FDG was injected through a tail vein catheter.…”
Section: Methodsmentioning
confidence: 99%